Integrasi Ekonomi Kreatif dan Bisnis Digital sebagai Determinan Green Entrepreneurship Intention Mahasiswa Generasi Z - Camelia Safitri (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The transition toward a green economy requires higher education institutions to play a strategic role in fostering sustainable entrepreneurship. Generation Z students have strong potential to become green entrepreneurs due to their adaptability to technology and heightened environmental awareness. This study examines the effect of integrating creative economy and digital business learning on Generation Z students’ green entrepreneurship intention using the Theory of Planned Behavior (TPB) framework. A quantitative approach was employed with Structural Equation Modeling (SEM) for data analysis. Data were collected from university students who had completed courses in creative economy as well as digital economy and business. The findings indicate that creative economy learning has a significant effect on environmental awareness, while digital business learning has a significant effect on green entrepreneurial attitudes. Environmental awareness and green entrepreneurial attitudes were found to partially mediate the relationship between learning integration and green entrepreneurship intention. These results highlight the importance of integrating creative economy and digital business curricula in higher education to promote green entrepreneurship among Generation Z students.